Genetically engineering Shewanella oneidensis MR-1 to improve the performance of microbial fuel cells - Zhang, Lei (2017)
The development of sustainable and renewable power supplies is one of the most pressing issues in modern society, due to the rapid depletion of fossil fuels. Microbial electrochemical techniques, such as microbial fuel cells (MFCs), offer an attractive solution because they can couple the production of bioelectricity with processes such as bioremediation or wastewater treatment. Shewanella oneidensis MR-1 is one of the most widely used microbial hosts in MFCs due to its versatile metabolic capabilities. It is capable of oxidizing different organic compounds and transferring intracellular electrons through its cell membrane to the anode of the MFC, thereby resulting in the flow of an electrical current. Despite their obvious potential, present-day MFCs have a limited range of industrial applications and are not widely adopted largely because they suffer from a low power output. In this PhD work, different strategies have been applied to genetically engineer Shewanella oneidensis MR-1 in order to enhance the bioelectricity production capability of MFCs. Lactate is the primary substrate utilized by Shewanella oneidensis MR-1 to survive and strive in natural environment. In MFCs operations, lactate is the ultimate electron donor for bioelectricity generation. However, Shewanella oneidensis MR-1 has low efficiency in consuming lactate under MFC operation condition. Thus, genes encoding lactate permease and lactate dehydrogenase have been introduced and overexpressed in MR-1 with the aim of enhancing the lactate consumption rate and eventually improve electricity output in MFCs operations. Strain SP-1 had the best performance among all the resultants and was selected to generate mutant libraries for further screening. A mutant strain 7M6-SH8 was discovered to have the highest maximum power density output of 118.58±2.67mW/m2, which was 2.8 times of that attained by the control strain (42.03±6.59mW/m2). Moreover, MFCs inoculated with 7M6-SH8 achieved a Coulombic efficiency of 16.69%, which was ~2.2 times of that obtained by the control strain (7.77%). Catalytic current densities achieved from both mediated and direct electron transfer pathways by the mutant strain were significantly higher than the control strain with 3.1-fold and 2.7-fold increases, respectively. Quantitative real-time reverse transcription PCR results also showed that genes encoding proteins in the electron generation and transport pathways have increased expressions, and SEM images showed that biofilm formation on the electrode surface was much thicker than the control strain. Overall, the engineered strain has improved the consumption and utilization of lactate, increased the efficiency of electron transfer in different pathways, and enhanced biofilm formation on the anode electrode surface. Compared with extracellular electron transfer, the intracellular electron generation and transport has not drawn enough attention among studies of Shewanella oneidensis MR-1. In the search of relevant proteins in the intracellular electron transfer pathway, computational approaches were adopted to conduct genome-scale metabolic modeling of Shewanella oneidensis MR-1. The hya genes were shown to have the highest potential in enhancing electricity generation. NADH is the intracellular electron carrier. Thus, the hya genes and ndh encoding NADH dehydrogenase were selected for overexpression in MR-1. Results showed that the co-overexpression of hyaA and ndh in the strain plac-hyaA-Ptac-MT12(IPTG_1.0mM) achieved a maximum power density of 112.00±1.77mW/m2, which was 2.8 times of that attained by the control strain (40.22±1.92mW/m2). Moreover, it achieved a Coulombic efficiency of 18.59%, which was 2.4 times of that obtained by the control strain (7.85%). Catalytic current density via direct electron transfer pathway was significantly increased with a 3.86-fold change. Anode efficiency is one of the limiting factors in electricity output in MFCs. Improving the efficiency in the extracellular electron transfer (EET) is highly demanded for the further improvement in MFCs operations. In recent decades, the popularly studied pathway in Shewanella oneidensis MR-1 is the metal-reducing (Mtr) pathway with several important relevant c-type cytochromes. Herein, we have overexpressed the most studied c-type cytochromes in MR-1, and the resultant achieved a maximum power density of 88.41±1.09mW/m2, which was 2.14 times of that attained by the control strain (41.30±1.23mW/m2). Moreover, it achieved a Coulombic efficiency of 15.48%, which was 1.94 times of that obtained by the control strain (7.98%). Catalytic current density via direct electron transfer pathway was significantly increased with a 3.82-fold change. In order to achieve scalable control of gene expressions in Shewanella oneidensis MR-1 and flexible operation in MFCs, a library of genetic parts that is usable for Shewanella oneidensis MR-1 is of high demand. We have generated mutagenesis library of a ribosome binding site, and characterized several terminators as well as constitutive and inducible promoters in MR-1 in order to initiate a library construction.